Intrinsic Efficiency Calibration for Uranium Isotopic Analysis in Soil Samples - Bui, Van Loat (H. : ĐHQGHN, 2017)
In this work, we present the results of using the non-destructive gamma spectroscopic method for uranium isotopic analysis and checking the status of radioactive equilibrium between 238U and 226Ra in soil samples. In order to analyze uranium isotopes and check the status of equilibrium between 238U and 226Ra the activity ratios 235U/238U and 238U/226Ra were measured. The these activity ratios were determined based on the characteristic gamma rays and using intrinsic (relative) detection efficiency calibration method. The results obtained shows that this suggested analytical method can be used to determine the uranium concentration in the case of the samples having arbitrary shapes and it does not require the use of any reference materials.